Same, same but different? How democratically elected right-wing populists shape climate change policymaking. Issue 5 (29th July 2022) - Marquardt, Jens; Oliveira, M. Cecilia; Lederer, Markus
ABSTRACT: The Paris Agreement expresses far-reaching commitments to combat climate change, but its translation into national contexts faces severe confrontation by populist movements and individuals worldwide. We unpack and compare how differently right-wing populist leaders translate rhetoric into climate policymaking and institutional change. We do so by investigating three areas of contestation: (1) the economic marginalization of the left behind, (2) conflicts between globalism and nationalist priorities, and (3) tensions between universalized science and situated experiences. We offer an analytical framework to study how right-wing populist leaders shape climate policymaking and test the approach with empirical observations from three democratically elected right-wing populists in the US, the Philippines, and Brazil. Populists severely affect climate policies in the long run, but these effects are highly context-specific. Engaging with populist climate politics needs to more seriously respond to local contexts and distinguish between the economic, anti-elitist, and knowledge foundations it is intertwined with.